Revitalizing ecotourism for a sustainable tasik chini biosphere reserve - Mohd Ekhwan, Toriman; Habibah, Ahmad; Mushrifah, Idris (2013)
Ecotourism is often perceived as an excellent tool for promoting sustainable development in most of the protected and special areas, including the Biosphere Reserve (BR). In fact, ecotourism can help to revive a declining tourist destination as it preserves nature and support rehabilitation and most importantly, it fits well with the Biosphere Reserve functions of conservation, development and logistics. This article aims to analyse the life cycle of Tasik Chini as an ecotourism destination, by focusing on the following aspects, namely travel engagement, ecotourism approaches and revitalization initiatives. This study utilized a mixed method approach by combining the primary and secondary data in tracing the evolution, development and the existing stage of ecotourism. The study reveals that the four major components which drive ecotourism program/initiatives toward achieving sustainable development are the state of ecotourism in the BR, the targeted segments of the community, the extent of community involvement as well as the supportive infrastructure for ecotourism. As ecotourism in the BR significantly promotes learning and research, smart partnership or collaboration between the stakeholders will help generate true eco-tourists. It is therefore imperative that ecotourism initiatives in the context of the BR is revitalised as it will enable a reflective analysis of the destination’s life cycle. The intervention of credible initiatives can fulfil the real and future roles of ecotourism in sustainable development.